ANALISIS FENOMENA FLEXING PADA VIDEO SULTAN MEDAN BELI MOBIL LISTRIK TESLA JAM 3 PAGI!! #MURAHBANGET DI KANAL YOUTUBE INDRA KENZ - Firstiyanti, Aulia (Jurnal Ilmiah Multidisiplin, 2023)
We live in a world where status is determined by wearing a logo, driving a sports car, and/or listening on AirPods. This is closely related to the role of social media and conspicuous consumption. This consumption model is called flexing by today's virtual world community. In this study, the authors analyzed the phenomenon of flexing (show-off culture) and packaged it in a journal entitled Flexing pada Video Sultan Medan Beli Mobil Listrik Tesla Jam 3 Pagi!! #MurahBanget di Kanal YouTube Indra Kenz. The writer tries to examine flexing symbols using Charles Sanders Peirce's semiotics. This study applies qualitative methods by sorting and selecting qualified data and then analyzing it. The conclusion is that the representation of conspicuous consumption contained in the video "Sultan Medan Buys Tesla Electric Car at 3 AM #MurahBanget" is shown clearly through the signs and meanings in it, so we can see the purpose of this video being published, namely showing social status, creating an impression on other people, and showing ability.